Imagine! assessments that energize students - Stiggins, Rick; Assessment Training Institute (Portland, Oregon : Assessment Training Institute, 1999)
A training video in which Dr. Stiggins presents a dynamic redefinition of the relationship between assessment and student motivation. He suggests that educators' success in a standards-driven educational environment hinges on our ability to help all students believe that they are capable learners
Title from cover
Presenter: Rick Stiggins
Keywords: Educational tests and measurements -- United States; Educational evaluation -- United States; Students -- Rating of -- United States; Effective teaching -- United States; Teacher effectiveness -- United States